TERRITORIAL IMAGE AND BRANDING AS TOOLS FOR DEVELOPING WESTERN KAZAKHSTAN AS A TOURIST DESTINATION - Sergeyeva, Aigul M.; Omirzakova, Miroslava Zh.; Zhakuda, Gulsezim N.; Telekeshov, Khamit A. (Journal of the Geographical Institute “Jovan Cvijić” SASA, 2021)
With the development of tourism, it has been necessary modernization of ways on being attended by tourists. Comparatively new method of influencing to a customer is branding, has been the most significant process in terms of promotion, which identify features of exact territory in contribution of competitive activities for being attractive for tourists. The article is aimed to identify the existing and promising tourist brands of Western Kazakhstan. Since territorial branding is a key factor in the development of tourism industry, the authors conducted a survey among respondents from different regions of Kazakhstan to identify potential tourist brands, main associations, as well as challenges and opportunities for recreation and tourism. The research was carried out using the Google Forms platform and sociological survey. The research results prove that there are unofficial leading brands in the region, which are likely to become the region’s official tourist symbols. Besides, both favorable and unfavorable factors for recreation demonstrate the controversial development of tourism industry in the research area. Creation, development, and promotion of a tourist brand plays an important role in the tourism and recreation area. This contributes to strengthening the tourist destination image in the tourism market.